Through the critical thinking of Filiberto Menna: the reorganization of the Filiberto and Bianca Menna Foundation library - Alberto Landi (Bibliothecae.it, 2025)
This article reports the experience of the reorganization and inventorying of the library of the Filiberto and Bianca Menna Foundation - Center for the Study of Contemporary Art, located at the former Casa del Combattente in Salerno. The personal collection of Filiberto Menna, art critic and politically active intellectual, constitutes the main nucleus of the Foundation, established in 1989 following his death. The recent reorganization, which took place in 2024, represents an opportunity to include this important book collection in the broad debate regarding ‘author libraries’. First of all, an analysis of the contents of the forty shelves that make up the library was conducted, organizing a schematic work in which, for each shelf, the location and bibliographic information of each book unit are reported. The analysis of the material allowed us to restore Filiberto Menna’s interests, the creation and evolution of his critical thinking. The notes of ownership and the handwritten annotations present in the volumes outline an attentive reader, who loved to note down the suggestions that the texts aroused in him. Finally, an in depth analysis is reported regarding the notes of ownership and the dedications present within the book units, reported in the “Notes” section of the inventory work. The following article also presents the complete list of dedications in the appendix.